Role of D1 receptor antagonism in contextual fear learning and memory - Heath, Florence (2015)
Understanding the modulation of contextual fear learning and memory by the neurotransmitter dopamine is important as it could lead to a greater understanding of the mechanisms underlying anxiety disorders. The effect of D1 receptor antagonism during the contextual fear learning and memory stages was investigated. In the first set of experiments the D1 receptor antagonist SCH 23390 (0.1mg/kg; i.p.) was administered systemically before or immediately after contextual fear conditioning to determine whether D1 receptors are involved in the acquisition and/or consolidation stages. This experiment was followed up by investigating the effects of SCH 23390 infusion into the dorsal hippocampus (5μg per side) or amygdala (2.5μg per side) on contextual fear acquisition. The second set of experiments investigated the involvement of systemic SCH 23390 in the reconsolidation, retrieval, destabilization and extinction of contextual fear. SCH 23390 was administered before or immediately after either a short reactivation or longer extinction session. In the destabilization experiment SCH 23390 was administered prior to reactivation and the NMDA receptor antagonist MK-801 (0.1mg/kg; i.p) immediately after to determine if SCH 23390 could rescue the amnesic effects of NMDA receptor antagonism. It was found that systemic and intra-hippocampal but not intra-amygdala SCH 23390 reduced freezing during memory retention testing, twenty four hours and seven days after conditioning. There was no effect of SCH 23390 when immediately given after conditioning. There was also no effect of SCH 23390 when given either before or after reactivation or extinction sessions. The destabilization experiment was inconclusive as MK-801 was not found to impair memory when administered after reactivation. In conclusion, D1 receptors were found to be involved in the acquisition of contextual fear, and this modulation was found to occur in the dorsal hippocampus but not the amygdala. D1 type receptors were not found to be involved in the consolidation, retrieval, reconsolidation or extinction of contextual fear.